1978
DOI: 10.21273/jashs.103.1.142
|View full text |Cite
|
Sign up to set email alerts
|

Winter Rainfall Reduces Rest Period of Apple and Pear1

Abstract: Repeated winter rain or water soaking in the laboratory reduced the time required for breaking winter rest of ‘Bartlett’ pear (Pyrus communis L.) and ‘Starkrimson’ apple (Malus domestica Borkh.). Possibly a water soluble inhibitor is leached from the buds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…That apple shoots also must be chilled indicates some changes occur within the buds which enhance effectiveness of root cytokinins. These changes may involve a reduction of growth inhibitors in the bud or bud scales (18,22), and/or a change in sensitivity of the bud tissues (19). Chilling the root or shoot alone is partially effective in promoting budbreak in apple, but the results thus far indicate both must be chilled for maximum budbreak to occur.…”
Section: Discussionmentioning
confidence: 99%
“…That apple shoots also must be chilled indicates some changes occur within the buds which enhance effectiveness of root cytokinins. These changes may involve a reduction of growth inhibitors in the bud or bud scales (18,22), and/or a change in sensitivity of the bud tissues (19). Chilling the root or shoot alone is partially effective in promoting budbreak in apple, but the results thus far indicate both must be chilled for maximum budbreak to occur.…”
Section: Discussionmentioning
confidence: 99%
“…Since they failed to predict the date of the rest termination for the sprinkled treatment using various models (7), they suggest that other factors are also involved in breaking bud rest when using overhead sprinkling. It still could be that the models used are not accurate enough or that the cause for the response observed could have been other than reduced daytime tem perature, as proposed by Westwood and Bjornstad (9). They claim that leaching of growth retardants would be responsible for better budbreak under rainy conditions.…”
mentioning
confidence: 99%
“…Recent studies have indicated that differences in bloom date are greater than predicted by accumulation of chill units (2,5). This discrepancy in time required for breaking rest may be a result of leaching of some water-soluble substance(s) from the dormant tree (12). Increased water in the root zone of sprinkled trees may also contribute to the observed response.…”
mentioning
confidence: 99%